Chemical Contents and Antifungal Activity of Some Durable Wood Extractives vs. Pleurotus ostreatus - Ateş, Saim; Gür, Mahmut; Özkan, Osman E.; Akça, Mehmet; Olgun, Cağrı; Güder, Aytaç (BioResources, 2015)
The total phenolic content (TPC), total flavonoid content (TFC), phenolic compounds, and antifungal activity of olive (Olea europaea var. sylvestris) and juniper (Juniperus foetidissima) sapwood and heartwood extractives were examined. The extractives were obtained using methanol solvents. The different compounds in extractives were identified and quantified. The antifungal activities of different parts of the olive and juniper wood extractives were determined in vitro. Pleurotus ostreatus mycelium was used for the antifungal activity experiment. Extractive compounds obtained from olive and juniper woods were found to be effective, natural antifungal agents.
Keywords: Total phenolic contents; Olive; Antifungal activity; Juniper; Total flavonoid contents; TP248.13-248.65; Biotechnology; 3. Good health